From “Incel” to “Saint”: Analyzing the violent worldview behind the 2018 Toronto attack - Baele, Stéphane J. (Terrorism and political violence, 2021)
This paper combines qualitative and quantitative content analysis to map and analyze the “Incel” worldview shared by members of a misogynistic online community ideologically linked to several recent acts of politically motivated violence, including Alek Minassian’s van attack in Toronto (2018) and Elliot Rodger’s school shooting in Isla Vista (2014). Specifically, the paper analyses how support and motivation for violence results from the particular structure this worldview presents in terms of social categories and causal narratives.